Tribological degradation and corrosion of grinding disc wear contaminants in food - Segun Isaac Talabi; Ismaila Idowu Ahmed; Raheem Abolore Yahya; Taiwo Yahaya; Jeleel Adekunle Adebisi; Rasheedat Modupe Mahamood; Jamiu Kolawole Odusote; Mariam Kehinde Sulaiman; Lawrence Aderemi Olatunji; Sulaiman Abdulkareem (Results in Engineering, 2025)
In Africa and Asia, methods for grains size reduction to powder and paste is dominated by motorized grinding machine. Consequently, metal contaminants are inadvertently consumed in ground foods without a detailed understanding of their quantity, quality, degradability and health risks. The aim of this study was to conduct qualitative and quantitative assessments of metallic contaminants in processed maize following wet and dry grinding operations, with discs from different manufacturing processes. Again, the corrosion susceptibility of the metallic contaminants generated in ground food and simulated gastro-intestinal environments were also investigated. Six grinding discs produced using three manufacturing methods were used for maize grinding in wet and dry conditions. The chemical and phase compositions of the discs and metallic wear contaminants were determined using X-ray fluorescence spectroscope and X-ray diffractometer respectively. Corrosion susceptibility of metallic contaminants, in deionised water, ground maize water solution and simulated gastro-intestinal solution, were studied using electrochemical potentiodynamic polarisation scan and gasometric methods. Results showed that all discs, irrespective of the manufacturing process generated varying amounts of metallic contaminants in different morphologies. Generally, dry grinding generated significantly higher quantities of metallic contaminants than wet grinding. Furthermore, it was observed that metallic contaminant was less corrosive and stable in ground maize, while exponential corrosion rate occurred in simulated gastric solution. This study is relevant to food industries, which should be more concerned about food contamination in line with the UN SDG goal 3 on healthy living and promotion of well-being.